Al-Umm Madrasah al-Ula: Pembacaan Kritis atas Kompleksitas Kesehatan Mental Ibu dan Implikasinya terhadap Pedagogi Moral dalam Pendidikan Islam - Rofikasari Mutmainah; Alfan Nawaziru Zahara (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2025)
This article critically examines the relationship between motherhood, mental health, and Islamic education through the framework of moral pedagogy. Departing from the dominant idealization of mothers as al-umm madrasah al-?l? (the first school), the study questions how this normative construct operates within contemporary Islamic educational discourse and how it shapes mothers’ psychological experiences. Employing a library research method with an integrative theoretical review design, the analysis synthesizes scholarship from motherhood studies, mental health research, sociology of education, and Islamic education. The findings demonstrate that Islamic education often frames motherhood as a moral-pedagogical project that personalizes educational responsibility and positions mothers as the primary agents of children’s moral development. This construction generates structural mental health consequences, including chronic stress, emotional exhaustion, and maternal burnout, rather than merely individual psychological problems. These burdens are further intensified by the unequal distribution of pedagogical responsibility, in which schools, religious institutions, and the state provide limited structural support. The article argues that maternal mental health constitutes a critical indicator of pedagogical justice within Islamic education and calls for a paradigmatic shift from the idealization of motherhood toward a more collective, equitable, and mental health–sensitive model of moral education.